Is housing a public health issue? A survey of directors of public health. Issue 6769 (19th January 1991) - Roderick, P; Victor, C; Connelly, J
Abstract : OBJECTIVE–To determine the views of directors of public health on the importance of housing for public health and their departments' and health authorities' participation in housing issues. DESIGN–Postal self administered questionnaire survey. SETTING–All district health authorities in England and health boards in Wales, Scotland, and Northern Ireland. SUBJECTS–All 221 district directors of public health in England and chief administrative medical officers in Wales, Scotland, and Northern Ireland. MAIN OUTCOME MEASURE–Response to questionnaire consisting of fixed and open ended questions on housing issues. RESULTS–The response rate was 89% (196/221). Housing was perceived as a major health problem by 33% (65/196) of directors. Positive responses were most likely from inner city districts. In 47% (93/196) of departments there was a formal time commitment to housing issues with a median time of one session/week (range one per month to 10 per week). The main function was allocation of medical priority for public sector rehousing. Overall, 73% (144/196) reported some participation in this process. Reported participation in joint care planning and links with non-statutory housing organisations were uncommon. 53% (104/196) of directors had included housing issues in their annual health report. In 16% (32/196) of districts specific services for the homeless had been set up. CONCLUSIONS–Although concern about the impact of current housing policy on public health was shown by a substantial number of directors, the main activity was still allocation of medical priority despite a background of increasing housing need and homelessness. The underlying need is for greater advocacy to produce a healthy housing policy for all, and the annual public health report could be used to promote this objective.